ADAPTIVE FRAMEWORK FOR ERP IMPLEMENTATION IN SMEs: Integration of Technology Acceptance Model, Resource-Based View, and Contingency Theory - Sidiq, Purnomo (RISTEC : Research in Information Systems and Technology, 2025)
Enterprise Resource Planning (ERP) implementation in Small and Medium Enterprises (SMEs) faces high failure rates due to the misalignment between existing frameworks and the unique characteristics of SMEs. This study aims to develop an adaptive framework to improve ERP implementation success in SMEs through comprehensive theoretical integration. A Design Science Research methodology was employed to integrate Technology Acceptance Model, Resource-Based View, and Contingency Theory into a unified framework. Data were collected through systematic literature review of 187 publications from 2020-2024 and expert assessment for theoretical validation. The research resulted in an adaptive framework with five integrated components: organizational readiness assessment, adaptive system modularization strategy, intelligent vendor selection, dynamic change management, and comprehensive success measurement. The framework demonstrates superior explanatory power compared to single-theory approaches and provides practical guidelines for contextually relevant ERP implementation. The study contributes to the development of Adaptive Implementation Theory and offers actionable solutions for SMEs digital transformation.